Taxonomic revision of Coniceromyia Borgmeier (Diptera: Phoridae), with the description of three new species from Brazil - Ament, Danilo César; Amorim, Dalton De Souza (Zootaxa, 2016)
The 55 known species of Coniceromyia are herein revised. Three new species from the Atlantic Forest in Brazil are described—C. apioneura, sp.nov., C. neofusca, sp.nov. and C. tanycrossa, sp.nov.—and fourteen species are redescribed. Most of the species have foreleg, wing, hind femur, and male terminalia illustrated. Characters previously unnoticed are described for the first time. Coniceromyia cubensis Brues, previously accepted as a synonym of C. latimana (Malloch), has its status reinstated. Taxonomic problems in the genus are addressed, including the condition of the damaged holotypes of C. boliviana Borgmeier and C. vespertilio Schmitz, and our inability to associate males with the female holotypes of C. arizonensis Borgmeier, C. fusca Borgmeier and C. grenadensis (Brues). The holotypes of Coniceromyia angularis Borgmeier & Prado and Coniceromyia laticosta Prado are considered to be lost.